Variasi Tugas dan Aktivitas Pembelajaran di Sekolah Dasar pada Masa Pandemi Corona - Lathifah Nurul Hidayah; Laili Etika Rahmawati; Lupita Sari Pitra Wardani (Jurnal Pendidikan Edutama, 2021)
Abstrak: This research aims (1) to identify task variations in elementary school during the corona pandemic; and (2) to identify learning activities in elementary school during the corona pandemic. This research approach is descriptive qualitative. The data of this research are the the forms of task and learning activities during the corona pandemic. The data source comes from elementary school teachers in the Boyolali area. Data collection in this research uses a questionnaire in the form of Google Forms. The data analysis in this research uses an interactive method. The results showed (1) the task variations in elementary school during the corona pandemic in the form of portfolios, practice, and exercise. Applications or media that are mostly used by elementary school teachers in giving assignments during the corona pandemic namely Whatsapp; and (2) the learning activities in elementary school during the corona pandemic is the provision of instructional videos from YouTube, questions and answers discussion through Whatsapp, and working on exercises. Keywords: task variations, learning activities, corona, online learning Abstrak: Penelitian ini bertujuan (1) mengidentifikasi variasi tugas di Sekolah Dasar pada masa pandemi corona; dan (2) mengidentifikasi aktivitas pembelajaran di Sekolah Dasar pada masa pandemi corona. Pendekatan penelitian ini adalah deskriptif kualitatif. Data penelitian ini adalah bentuk-bentuk tugas dan aktivitas pembelajaran pada masa pandemi corona. Sumber data berasal dari guru-guru SD di wilayah Boyolali. Pengumpulan data pada penelitian ini menggunakan kuesioner dalam bentuk Google Forms. Analisis data pada penelitian ini menggunakan metode interaktif. Hasil penelitian menunjukkan (1) variasi tugas di Sekolah Dasar pada masa pandemi corona berupa portofolio, praktik, dan soal latihan. Adapun aplikasi atau media yang banyak digunakan guru SD dalam memberikan tugas pada masa pandemi corona yaitu Whatsapp; dan (2) aktivitas pembelajaran di Sekolah Dasar pada masa pandemi corona ialah pemberian video pembelajaran dari Youtube, diskusi tanya jawab melalui aplikasi Whatsapp, dan mengerjakan soal latihan. Kata kunci: variasi tugas, aktivitas pembelajaran, corona, pembelajaran daring